ARDS as a presenting feature in sarcoidosis: an uncommon occurrence - Shrestha, Sanjeet K; Malla, Jonas; Bhusal, Yuvaraj; Bhattarai, Sanjeet; Lama, Rakesh; Rayamajhi, Sulav; Gurung, Naresh; Shrestha, Ashish; Karthik, Ashish; Pradhan, Pratistha; et al. (Nepalese Respiratory Journal, 2022)
Sarcoidosis though a chronic multi-system granulomatous disease, predominantly involves respiratory system. Often asymptomatic, patients can present with lymphadenopathy, prolonged fever and shortness of breath. Acute respiratory distress syndrome (ARDS) is relatively uncommon presenting feature of the disease. Here we present a case of a 19 years old female presenting in acute respiratory distress syndrome, eventually being diagnosed as Sarcoidosis. Although different diagnostic criteria have been developed for early diagnosis of sarcoidosis, atypical presentations can always pose significant challenge and lag for the diagnosis.